Herpes Simplex Virus Type 2 (HSV-2) and Cytomegalovirus (CMV) among Women with Macerated Stillbirth: A Cross-Sectional Hospital-Based Study from Mwanza, Tanzania - Helmut A. Nyawale; Elieza Chibwe; Fridolin Mujuni; Lidya Maiga; Albert Silvin; Alda Ester Chongo; Bertrand Msemwa; Vitus Silago; Mtebe Majigo; Doreen Kamori; Stephen E. Mshana; Mariam M. Mirambo (Journal of Pregnancy)
Background. Stillbirth adversely affects pregnancy outcomes in low- and middle-income countries (LMICs). Viral infections have been implicated as one of the causes of stillbirths. Despite high rates of stillbirths and high viral prevalence in LMICs, there is limited information regarding their association. This study investigated the magnitude of herpes simplex 2 virus (HSV-2) and human cytomegalovirus (HCMV) among women with macerated stillbirth. Methods. A cross-sectional hospital-based study was conducted involving 279 women with macerated stillbirth between July and August 2018 at different health facilities in Mwanza, Tanzania. Detection of HSV-2 was done by immunochromatographic test while that of HCMV was done using enzyme-linked immunosorbent assay (ELISA). Descriptive data analysis was done using STATA version 13. Results. A total of 28 (10.04%, 95% CI: 6.8-13.9) tested positive for HSV-2 IgG antibodies with only 4 (1.43%, 95% CL: 0.3-2.8) testing positive for HSV-2 IgM antibodies. HCMV IgG antibodies were detected in 131 (77.98%, 95% CI: 71-84) of 168 women tested. By multivariate logistic regulation analysis, advanced age (OR: 0.93, 95% CI: 0.87-0.99, p=0.025) was significantly associated with negative HSV-2 IgG antibodies. By log multinomial regression analysis, only urban residence (RRR.4.43: 95% CI 1.53-12.80, p=0.006) independently predicted HCMV IgG seropositivity among women with stillbirth. Twenty-one (30.9%) of women with positive HCMV IgG antibodies had low avidity index (<40%) indicating recent infection. Conclusion. Significant proportion of women with macerated stillbirth residing in urban and with low age have HCMV and HSV antibodies, respectively. This calls for the need to consider introducing screening of these infections in the Tanzanian antenatal package and further studies to explore the role of these viruses in causing stillbirth in Tanzania.